FRI0525 Elastographic Ultrasound of Metacarpophalangeal (MCP) Synovium in Rheumatoid Arthritis (RA). (15th July 2016) - Sammel, A.M.; Spies, M.C.; DeCarle, R.; Rayment, M.; Joshua, F.
Abstract : Background: Shear wave elastographic ultrasound (SW-EUS) assesses the stiffness of human tissues. It is used in liver, thyroid and breast imaging but has never before been studied in synovium. Soft tissues have a slower shear wave velocity (SWV) than stiff tissues. We hypothesised that rheumatoid arthritis (RA) patients would have softer synovium and thus slower SWV than controls. Objectives: The aim of the project was to establish a reproducible scoring system for synovial SW-EUS and use it to compare RA patients with controls. We also set out to assess if SWV varied with disease activity. Methods: A cross sectional study was conducted including nine RA patients and five age and sex matched controls. RA patients were recruited consecutively from a single rheumatology practice. Participants underwent a questionnaire, clinical examination, blood sampling, grey scale ultrasound (GSUS), power doppler ultrasound and SW-EUS ultrasound examination of MCP joints 2 - 5 on the dominant hand. Ultrasound was performed and scored by two blinded musculoskeletal trained sonographers. Results: The average age of participants was 60. The mean RA disease activity score (DAS28-ESR) was in the low to moderate range of 3.65 (range 2.4–7.4). Patients with RA had significantly lower maximum SWV than controls (6.38 m/s vs 6.99 m/s p=0.042). Negative Pearson's correlation coefficients (PCC) were observed between maximum SWV and a range of disease activity markers including GSUS graded synovial thickness (PCC = -0.57, p=0.03) and ESR (PCC = -0.46, p=0.095). SW-EUS had good intra- and inter-observer reliability with intraclass correlation coefficients of 0.66 and 0.58 for maximum SWV and >0.80 for colour scale rated average and minimum SWV. Conclusions: This is the first reported study of SW-EUS in synovial tissue. Maximum SWV was significantly lower in the synovium of RA patients compared with controls. There was a negative correlation between maximum SWV and GSUS graded synovial thickening suggesting that SWV may be lower in more active patients. SW-EUS may have a role in the diagnosis and assessment of disease activity in RA. Disclosure of Interest: None declared